Features of cognitive dysfunction in patients with depressive disorder and cerebrovascular pathology - Prokhorova, Olga (Psychosomatic Medicine and General Practice, 2017)
Background. In recent years, there has been an increase in the number of older adults, and, at the same time, the accumulation of mental and somatic diseases inherent in these age categories. Depression, dementia and cardiovascular disease continue to occupy leading positions. Executive dysfunction syndrome in patients with the organic depressive disorder and cerebrovascular pathology is one of the pathognomonic features of impairment of higher brain functions in subcortical ischemic depression, which is important for the prognosis of the disease, provision of timely medical care, development of preventive measures and improvement of patients' quality of life. Materials and methods. Using TMT and Stroop test, 138 patients with the depressive disorder were screened for cognitive dysfunction. Results. More pronounced cognitive dysfunction in the form of the impairment in executive function, cognitive control, volume and distribution of attention was observed in patients with organic depressive disorder and signs of subcortical ischemia of the GM. Differences in the structure of violations of cognition are caused by zones of morphological lesions in the GM and the rupture of cortico-strial paths. Conclusion. Thus, in patients with subcortical ischemic depression, there is a syndrome of executive dysfunction, which is the leading cause of subcortical ischemic dementia.